Reproductive hormones in infertility and infection in sub-saharan African males (2001)
The male factor is now recognised as a major contributor to a couples’ infertility. The role of reproductive hormones in male infertility is however controversial. This study therefore, was designed to investigate the role of reproductive hormones in male infertility in sub-Saharan Africa. 3 groups of subjects between 18-56 years were investigated. 25, 42 and 45 were recruited in fertile, infertile and sexually transmitted diseases (STDS). Follicle stimulating hormone (FSH), luteinising hormone(LH) and prolactin were estimated using the immunoradiometric assay technique while testosterone was estimated using radioimmunoassay technique utilizing commercially available kits (ICN Biomedical Inc.).Statistical analysis was done using students t-test and anova (one way) for comparison of means. FSH, LH, prolactin and testosterone were similar between fertile and infertile groups and between normospermic and dyspennic infertile groups. However, all except, prolactin were similar in STDs and fertile groups. Hormonal abnormalities may not be a major contributor to male infertility. However, role of prolactin in infertility and infection requires further studies.